Coffee consumption and colorectal cancer risk: a multicentre case-control study from Italy and Spain. Issue 3 (17th February 2021) - Rosato, Valentina; Guercio, Valentina; Bosetti, Cristina; Gracia-Lavedan, Esther; Villanueva, Cristina M.; Polesel, Jerry; Toffoluti, Federica; Moreno, Victor; Martin, Vicente; Aragonés, Nuria; Dierssen-Sotos, Trinidad; Olmedo-Requena, Rocío; et al.
Abstract : Background: Coffee contains many bioactive substances that can play a role on colorectal cancer. Epidemiological evidence of coffee intake and colorectal cancer is, however, inconsistent. Aim: To provide further information on the risk of colorectal cancer in relation to coffee consumption. Methods: Data derive from two companion case-control studies conducted in Italy and Spain within the European Union Project on Health Impacts of long-term exposure to disinfection by-products in Drinking Water and the Spanish Multi-Case Control study on Cancer. These included a total of 2289 incident cases with colorectal cancer and 3995 controls with information on coffee intake. Odds ratios (ORs) and the corresponding 95% confidence intervals (CIs) were derived from unconditional logistic regression models, adjusted for study centre, sex, age, education, smoking, and other covariates. Results: Compared with never coffee drinkers, the OR was 0.99 (95% CI 0.95–1.02) for total coffee consumption. There was no significant trend in risk with dose or duration, the ORs being 0.95 (95% CI 0.72–1.25) for an amount of five or more cups per day of coffee and 0.95 (95% CI 0.75–1.19) for a duration of consumption of 50 years or longer. The OR was 1.04 (95% CI 0.87–1.25) for two or more cups per day of decaffeinated coffee. There were no heterogeneity across strata of various covariates, as well as no apparent differences between various anatomical subsites. Conclusion: This large pooled analysis of two studies shows no association of coffee and decaffeinated coffee with colorectal cancer risk.